Diagnostic Value of Cardiac Magnetic Resonance Strain Analysis for Detection of Cardiac Sarcoidosis - Dabir, Darius; Meyer, David; Kuetting, Daniel; Luetkens, Julian; Homsi, Rami; Pizarro, Carmen; Nadal, Jennifer; Thomas, Daniel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose The aim of this study was to investigate the diagnostic value of cardiac magnetic resonance (CMR)-derived strain parameters in patients with sarcoidosis, and to compare results to standard CMR markers of sarcoidosis (edema/T2 ratio, early gadolinium enhancement, late gadolinium enhancement) for prediction of disease outcome.Materials and Methods 61 patients with biopsy-proven sarcoidosis underwent CMR examination. According to CMR results, patients were divided into two different groups: patients with (CMR+; n = 23) and without (CMR–; n = 38) findings consistent with cardiac sarcoidosis. In addition, a group of healthy age-matched volunteers (controls; n = 22) served as controls. Left ventricular functional parameters as well as left ventricular longitudinal and circumferential strain were evaluated in all three groups.Results Compared to controls, global longitudinal strain (GLS) was significantly impaired in patients with sarcoidosis, irrespective of cardiac involvement. No significant differences in GLS could be revealed between CMR+ and CMR– patients. Circumferential strain parameters were significantly impaired in CMR+ patients in comparison to CMR– patients and controls, while no significant differences could be revealed between CMR– patients and controls. GLS was significantly lower in patients with a negative outcome compared to controls. Compared to the rest of the CMR+ and CMR– patients, the GLS in patients with a negative outcome was further reduced but did not reach statistical significance.Conclusion GLS is the only strain parameter detecting left ventricular functional impairment in sarcoidosis patients with otherwise unsuspicious CMR and controls. GLS is further reduced in patients with a negative outcome. Thus, GLS may have the potential to serve as a marker for early cardiac involvement in sarcoidosis.Key points Citation Format
Keywords: cardiac; sarcoidosis; strain; feature-tracking